Modellbasierte Umsetzung des Anforderungsmanagements zur Unterstützung der Entwicklung eines Experimentalsatelliten - Gadzo, Emir; Mehlstäubl, Jan; Denk, Martin; Paetzold, Kristin (Proceedings of the 32nd Symposium Design for X, DFX 2021, 2021)
The needs and expectations of customers for a system are reflected in the requirements. The management of requirements therefore plays an important role in the product development process. In order to address the increasing complexity in product development and the resulting impact on requirements management, a model-based approach for the implementation of requirements management is needed in a satellite research project. In this paper, previous approaches for the implemen-tation of a model-based requirements management are systematically examined for their possibilities and limitations. Subsequently, a target-oriented concept for the model-based implemen-tation of requirements management for a satellite research project is subsequently derived.
Created from Fastlane, Scopus look-up
Keywords: Model based approach; Model based systems engineering (MBSE); Requirements management; Satellite research project; Systems engineering